Helicobacter hepaticus-Induced Colitis in Interleukin-10-Deficient Mice: Cytokine Requirements for the Induction and Maintenance of Intestinal Inflammation - Kullberg, Marika C. (American Society for Microbiology, 2001)
We have previously shown that specific-pathogen-free interleukin-10 (IL-10)-deficient (IL-10 KO) mice reconstituted with Helicobacter hepaticus develop severe colitis associated with a Th1-type cytokine response. In the present study, we formally demonstrate that IL-12 is crucial for disease induction, because mice deficient for both IL-10 and IL-12 p40 show no intestinal pathology following H. hepaticus infection. By using monoclonal antibodies (MAbs) to IL-12, gamma interferon (IFN-γ), and tumor necrosis factor alpha (TNF-α), we have further analyzed the role of these cytokines in the maintenance of the Th1 response and inflammation in IL-10 KO mice with established H. hepaticus-induced colitis. Treatment of infected colitic IL-10 KO mice with anti-IL-12 p40 resulted in markedly reduced intestinal inflammation, colonic IFN-γ, TNF-α, and inducible nitric oxide synthase (iNOS) mRNA levels, and H. hepaticus-specific IFN-γ secretion by mesenteric lymph node (MLN) cells compared to the findings in control MAb-treated mice. Moreover, the diminished pathology was associated with decreased numbers of colonic CD3(+) T cells and significantly reduced frequencies of Helicobacter-reactive CD4(+) Th1 cells in MLN. In contrast, anti-IFN-γ and/or anti-TNF-α had no effect on intestinal inflammation in IL-10 KO mice with established colitis. Using IL-10/IFN-γ double-deficient mice, we further show that IFN-γ is not required for the development of colitis follwing H. hepaticus infection. MLN cells from infected IL-10/IFN-γ KO animals secreted elevated amounts of IL-12 and TNF-α following bacterial antigen stimulation, indicating alternative pathways of disease induction. Taken together, our results demonstrate a crucial role for IL-12 in both inducing and sustaining intestinal inflammation through recruitment and maintenance of a pool of pathogenic Th1 cells.